Hábitos alimentarios, antropometría y presión arterial de adultos mayores hipertensos de un barrio en Bogotá (2022)
The identification of dietary habits, anthropometric measurement and blood pressure level are strategies for the detection of cardiovascular risk factors associated with hypertension. Objective: To describe the dietary habits, nutritional status by anthropometry and blood pressure level of older adults with arterial hypertension in a neighborhood in Bogotá D.C. Methodology: Quantitative, descriptive, cross-sectional study, with probabilistic sampling by clusters, carried out on 123 older adults from a population of 5382 people, using a characterization card, a validated questionnaire on eating habits in Colombia from the ENSIN 2015. In addition, anthropometry assessment was performed according to resolution 2465 of 2016 and blood pressure measurement as established by the American Heart Association (AHA) in 2017. Results: stage I arterial hypertension was more prevalent in women, but stage II arterial hypertension was higher in men, especially between 70 to 79 years, overweight was the anthropometric classification with the highest prevalence (44.7%), cardiovascular risk by waist circumference was very high in 60.2% of the population; most consume 5 meals a day, at home, live with family and have a low level of schooling. Conclusion: The present study allowed us to identify that overweight and the high intake of foods rich in carbohydrates, proteins and fats during the day at inadequate times were among the causes of arterial hypertension in stages I and II.